Cambridge Reading Adventures: Please Stop, Sara! (Pink A Band) - Kathryn Harper (Cambridge, United Kingdom Cambridge University Press, 2016)
Cambridge Reading Adventures is a book-banded international Primary reading scheme which couples an exciting range of text with precise bookbanding from the Institute of Education. Sara finds ways to make a noise. Can Adam stop her?
Nursery, Jr.Kg
Keywords: Cambridge Reading Adventures; Leveled Reader -- Leveled Reader